IMPROVING THE PEDAGOGICAL CONDITIONS FOR IMPROVING EDUCATIONAL AND METHODOLOGICAL SUPPORT FOR PRIMARY EDUCATION IN UZBEKISTAN - Ruzmetova Novval Vahabdjanovna; Abdullayeva Regina Avazbekovna (Bright Mind Publishing, 2026)
This article consists of developing methodology dedicated to pedagogical mastery among educators of primary education based on axiological approach. The main goal of this dissertation is to determine and analyze the conditions of formation the mastery of primary education teachers. Boosting assessment methodic of pedagogical skill in matters of moral education.
Keywords: Pedagogical mastery, axiological approach, conditions of mastery, moral education.